2013
DOI: 10.1016/j.cell.2013.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of a Putatively Druggable Class of Phosphatidylinositol Kinases Inhibits Growth of p53-Null Tumors

Abstract: SUMMARY Here, we show that a subset of breast cancers express high levels of the type 2 phosphatidylinositol-5-phosphate 4-kinases α and/or β (PI5P4Kα and β) and provide evidence that these kinases are essential for growth in the absence of p53. Knocking down PI5P4Kα and β in a breast cancer cell line bearing an amplification of the gene encoding PI5P4K β and deficient for p53 impaired growth on plastic and in xenografts. This growth phenotype was accompanied by enhanced levels of reactive oxygen species (ROS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
217
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(236 citation statements)
references
References 38 publications
12
217
1
Order By: Relevance
“…For example, stable knockout of Drosophila dPIP4K (orthologous to the highactivity PIP4K2A in higher species) results in a dramatic attenuation of Akt phosphorylation (20), whereas acute depletion of PIP4K2A in human leukocytes by RNAi results in increased Akt phosphorylation (19). No Akt phenotype was found in PIP4K2A knockout mice (21), but as far as we are aware, cells of the hematopoietic lineage were not studied there; another study from the same group elegantly showed the tissue variability of gene knockouts, with PIP4K2B knockout mice having enhanced insulininduced Akt phosphorylation in skeletal muscle and liver but not in white fat (22). Certainly, it is not unreasonable to suggest a particular role of PI5P4Kα in blood cells given that these are the only cells reported so far to have an excess of this enzyme over the other isoforms (23).…”
Section: Discussionmentioning
confidence: 99%
“…For example, stable knockout of Drosophila dPIP4K (orthologous to the highactivity PIP4K2A in higher species) results in a dramatic attenuation of Akt phosphorylation (20), whereas acute depletion of PIP4K2A in human leukocytes by RNAi results in increased Akt phosphorylation (19). No Akt phenotype was found in PIP4K2A knockout mice (21), but as far as we are aware, cells of the hematopoietic lineage were not studied there; another study from the same group elegantly showed the tissue variability of gene knockouts, with PIP4K2B knockout mice having enhanced insulininduced Akt phosphorylation in skeletal muscle and liver but not in white fat (22). Certainly, it is not unreasonable to suggest a particular role of PI5P4Kα in blood cells given that these are the only cells reported so far to have an excess of this enzyme over the other isoforms (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these kinases control the level of certain PI monophosphates such as PI(5)P, which appears to function as a stress signal (6). Mutations in PIPKs have been linked to human diseases (7,8), and, in cancerous cells, the activities of PIPKs are often up-regulated, usually as a consequence of overexpression (9,10).…”
mentioning
confidence: 99%
“…Among the PIPKs, PI3Ks are the best-characterized enzymes that commonly are targets for anticancer drugs (8). Less is known about PI-4-phosphate 5 kinases (PIP5Ks), enzymes that are upstream of PI3K (9,10). The PIP5K family of lipid kinases consists of the three isozymes α, β, and γ (11)(12)(13).…”
mentioning
confidence: 99%